Posłowie polscy w Berlinie w dyskusjach wokół Aktu 5 Listopada 1916 roku w organach ustawodawczych Prus i Rzesz y Niemieckiej = Polish MPs in Berlin discussing the Act of 5 November 1916 in the legislative Dobies of Prussia and the German Empire - Nodzyński, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents an analysis of the parliamentary speeches made by the Polish MPs in the Parliament of Prussia and the German Empire on the Act of 5 November 1916. In this act Germany and Austro-Hungary announced the restoration of the Kingdom of Poland. To sum up the opinions expressed by the Polish opposition MPs, mainly ones associated with National Democracy and conservative loyalists, it is possible to say that the former were sceptical about the Act of 5 November and had a number of objections, whereas the latter accepted the Act with great satisfaction as a step towards Polish independence.
Keywords: posłowie polscy; Berlin; Prusy; Rzesza Niemiecka; Akt 5 Listopada 1916 roku; Polish MPs; Prussia; German Empire; Act of 5 November 1916